Superficial composition engineering for oxide nanoparticles derived Cu2ZnSn(S, Se)4 solar cells by a three-step annealing process. (15th November 2019) - Cai, Huiling; Yao, Liquan; Xia, Yingsen; Dao, Chunyan; Li, Jianmin; Lin, Limei; Huang, Zhiping; Chen, Guilin
Highlights: A three-step annealing process was designed to optimize the surface elemental constitution of CZTSSe. The addition of slight sulfur results in a significant increase of Voc without significantly sacrificing the J sc . The efficiency of oxide NP derived CZTSSe device increases from 4.71% (2-step) to 6.37% (3-step). Abstract: In this work, a three-step (sulfurization-selenization-sulfurization) annealing process was designed to optimize the surface constitution of Cu2 ZnSn(S, Se)4 (CZTSSe) thin films, which was prepared by oxide nanoparticles-based approach. The devices with the Mo/CZTSSe/CdS/ZnMgO/ZnO:Al/Al structure were fabricated and their performances were studied. The additional post-sulfurization with low toxicity sulfur powder has negligible impact on the structure, morphology and composition of CZTSSe bulk, however, it improves open circuit voltage of device significantly. The open circuit voltage can be increased significantly from 408 mV (without surface sulfurization) to 497 mV (with surface sulfurization). This is benefited from the increase of surficial sulfur content and the broadening of the surface band-gap of the CZTSSe thin film. The result is confirmed by X-ray photoelectron spectroscopy analysis. Such a crucial three-step annealing process promotes the power conversion efficiency from 4.71% (2-step) to 6.37% (3-step), which is the champion efficiency of oxide precursor derived CZTSSe solar cell.